Bivariate analysis of basal serum anti-Müllerian hormone measurements and human blastocyst development after IVF - Sills E Scott; Collins Gary S; Brady Adam C; Walsh David J; Marron Kevin D; Peck Alison C; Walsh Anthony PH; Salem Rifaat D (BMC, 2011)
Abstract Background To report on relationships among baseline serum anti-Müllerian hormone (AMH) measurements, blastocyst development and other selected embryology parameters observed in non-donor oocyte IVF cycles. Methods Pre-treatment AMH was measured in patients undergoing IVF (n = 79) and retrospectively correlated to in vitro embryo development noted during culture. Results Mean (+/- SD) age for study patients in this study group was 36.3 ± 4.0 (range = 28-45) yrs, and mean (+/- SD) terminal serum estradiol during IVF was 5929 +/- 4056 pmol/l. A moderate positive correlation (0.49; 95% CI 0.31 to 0.65) was noted between basal serum AMH and number of MII oocytes retrieved. Similarly, a moderate positive correlation (0.44) was observed between serum AMH and number of early cleavage-stage embryos (95% CI 0.24 to 0.61), suggesting a relationship between serum AMH and embryo development in IVF. Of note, serum AMH levels at baseline were significantly different for patients who did and did not undergo blastocyst transfer (15.6 vs. 10.9 pmol/l; p = 0.029). Conclusions While serum AMH has found increasing application as a predictor of ovarian reserve for patients prior to IVF, its roles to estimate in vitro embryo morphology and potential to advance to blastocyst stage have not been extensively investigated. These data suggest that baseline serum AMH determinations can help forecast blastocyst developmental during IVF. Serum AMH measured before treatment may assist patients, clinicians and embryologists as scheduling of embryo transfer is outlined. Additional studies are needed to confirm these correlations and to better define the role of baseline serum AMH level in the prediction of blastocyst formation.